Document Archiving Management for Jayamulya Village Apparatus, Kroya District, Indramayu Regency - Putri Zakiyatil Miskiyat; Putri Rahmah Nurfadhilah; Ati Agustin; Dini Safitri (Diplomasi : Jurnal Demokrasi, Pemerintahan dan Pemberdayaan Masyarakat, 2025)
This study explores the socialization of archival management in Jayamulya Village, Kroya District. Efficient and effective archival management is crucial for government administration and public service. However, many villages, including Jayamulya, face challenges in systematically managing archives. This research examines the socialization process undertaken by the village government to enhance understanding and skills of both the community and village officials in proper archival techniques. The methodology includes interviews, observations, and document analysis. Findings indicate that while socialization has raised awareness and understanding, implementation faces challenges such as inadequate facilities and lack of ongoing training. Recommendations include the need for additional support through more comprehensive training and improved facilities for archival management at the village level.